Differentiation of peripheral nerve sheath tumors in patients with neurofibromatosis type 1 using diffusion-weighted magnetic resonance imaging. Issue 4 (28th November 2018) - Well, Lennart; Salamon, Johannes; Kaul, Michael G; Farschtschi, Said; Herrmann, Jochen; Geier, Karin I; Hagel, Christian; Bockhorn, Maximilian; Bannas, Peter; Adam, Gerhard; Mautner, Victor F; Derlin, Thorsten
Abstract: Background: We sought to determine the value of diffusion-weighted (DW) magnetic resonance imaging (MRI) for characterization of benign and malignant peripheral nerve sheath tumors (PNSTs) in patients with neurofibromatosis type 1 (NF1). Methods: Twenty-six patients with NF1 and suspicion of malignant transformation of PNSTs were prospectively enrolled and underwent DW MRI at 3T. For a set of benign ( n = 55) and malignant ( n = 12) PNSTs, functional MRI parameters were derived from both biexponential intravoxel incoherent motion (diffusion coefficient D and perfusion fraction f ) and monoexponential data analysis (apparent diffusion coefficients [ADCs]). A panel of morphological MRI features was evaluated using T1- and T2-weighted imaging. Mann–Whitney U -test, Fisher's exact test, and receiver operating characteristic (ROC) analyses were applied to assess the diagnostic accuracy of quantitative and qualitative MRI. Cohen's kappa was used to determine interrater reliability. Results: Malignant PNSTs demonstrated significantly lower diffusivity ( P < 0.0001) compared with benign PNSTs. The perfusion fraction f was significantly higher in malignant PNSTs ( P < 0.001). In ROC analysis, functional MRI parameters showed high diagnostic accuracy for differentiation of PNSTs (eg, ADCmean, 92% sensitivity with 98% specificity, AUC 0.98; Dmean, 92% sensitivity with 98% specificity, AUC 0.98). By contrast, morphological imaging features had only limited sensitivity (18–94%) and specificity (18–82%) for identification of malignancy. Interrater reliability was higher for monoexponential data analysis. Conclusion: DW imaging shows better diagnostic performance than morphological features and allows accurate differentiation of benign and malignant peripheral nerve sheath tumors in NF1.